Enhancing the sensitivity of a standard plasmonic MIM square ring resonator by incorporating the Nano-dots in the cavity - Butt, Muhammad Ali ALI; Kazanskiy, Nikolay (Photonics Letters of Poland, 2020)
We studied the metal-insulator-metal square ring resonator design incorporated with nano-dots that serve to squeeze the surface plasmon wave in the cavity of the ring. The E-field enhances at the boundaries of the nano-dots providing a strong interaction of light with the surrounding medium. As a result, the sensitivity of the resonator is highly enhanced compared to the standard ring resonator design. The best sensitivity of 907 nm/RIU is obtained by placing seven nano-dots of radius 4 nm in all four sides of the ring with a period (ᴧ)= 3r. The proposed design will find applications in biomedical science as highly refractive index sensors. Full Text: PDF References: Z. Han, S. I. Bozhevolnyi. "Radiation guiding with surface plasmon polaritons", Rep. Prog. Phys. 76, 016402 (2013). [CrossRef] N.L. Kazanskiy, S.N. Khonina, M.A. Butt. "Plasmonic sensors based on Metal-insulator-metal waveguides for refractive index sensing applications: A brief review", Physica E 117, 113798 (2020). [CrossRef] D.K. Gramotnev, S.I. Bozhevolnyi. "Plasmonics beyond the diffraction limit", Nat. Photonics 4, 83 (2010). [CrossRef] A.N.Taheri, H. Kaatuzian. "Design and simulation of a nanoscale electro-plasmonic 1 × 2 switch based on asymmetric metal–insulator–metal stub filters", Applied Optics 53, 28 (2014). [CrossRef] P. Neutens, L. Lagae, G. Borghs, P. V. Dorpe. "Plasmon filters and resonators in metal-insulator-metal waveguides", Optics Express 20, 4 (2012). [CrossRef] M.A. Butt, S.N. Khonina, N. L. Kazanskiy. "Metal-insulator-metal nano square ring resonator for gas sensing applications", Waves in Random and complex media [CrossRef] M.A.Butt, S.N.Khonina, N.L.Kazanskiy. "Hybrid plasmonic waveguide-assisted Metal–Insulator–Metal ring resonator for refractive index sensing", Journal of Modern Optics 65, 1135 (2018). [CrossRef] M.A.Butt, S.N. Khonina, N.L. Kazanskiy, "Highly sensitive refractive index sensor based on hybrid plasmonic waveguide microring resonator", Waves in Random and complex media [CrossRef] Y. Fang, M. Sun. "Nanoplasmonic waveguides: towards applications in integrated nanophotonic circuits", Light:Science & Applications 4, e294 (2015). [CrossRef] H. Lu, G.X. Wang, X.M. Liu. "Manipulation of light in MIM plasmonic waveguide systems", Chin Sci Bull [CrossRef] J.N. Anker et al. "Biosensing with plasmonic nanosensors", Nature Materials 7, 442 (2008). [CrossRef] M.A.Butt, S.N. Khonina, N.L. Kazanskiy. Journal of Modern Optics 66, 1038 (2019).[CrossRef] Z.-D. Zhang, H.-Y. Wang, Z.-Y. Zhang. "Fano Resonance in a Gear-Shaped Nanocavity of the Metal–Insulator–Metal Waveguide", Plasmonics 8,797 (2013) [CrossRef] Y. Yu, J. Si, Y. Ning, M. Sun, X. Deng. Opt. Lett. 42, 187 (2017) [CrossRef] B.H.Zhang, L-L. Wang, H-J. Li et al. "Two kinds of double Fano resonances induced by an asymmetric MIM waveguide structure", J. Opt. 18,065001 (2016) [CrossRef] X. Zhao, Z. Zhang, S. Yan. "Tunable Fano Resonance in Asymmetric MIM Waveguide Structure", Sensors 17, 1494 (2017) [CrossRef] J. Zhou et al. "Transmission and refractive index sensing based on Fano resonance in MIM waveguide-coupled trapezoid cavity", AIP Advances 7, 015020 (2017) [CrossRef] V. Perumal, U. Hashim. "Advances in biosensors: Principle, architecture and applications", J. Appl. Biomed. 12, 1 (2014)[CrossRef] H.Gai, J. Wang , Q. Tian, "Modified Debye model parameters of metals applicable for broadband calculations", Appl. Opt. 46 (12), 2229 (2007) [CrossRef]